Knowledge of Atrial Fibrillation and Stroke Prevention: Development of Questionnaire and Validation of Results - Sahimi, Mohamed; Tariq, Abdul Razak; Rosnani, Hashim; Mohd Ali, Z. (Sage, 2016)
Bacground: Atrial fibrillation (AF) patients are 5 times more likely to have stroke than non-AF patients. Stroke prevention (SP) using anticoagulation therapy was recommended in AF patients. Knowledge about AF and SP (KAFSP) is one of the essential factors that can improve patients’ adherence. Yet no established studies were found to determine patients’ KAFSP among AF patients. Objectives: To develop and validate the questionnaire used to measure KAFSP. Methods: A cross-sectional survey was conducted in 4 hospitals in Malaysia. The psychometric of the KAFSP Questionnaire (KAFSP-Q) were performed using content validity index (CVI), internal consistency, test-retest, exploratory factor analysis (EFA), and sensitivity test. Results: A total of 304 patients completed a face-to-face interview to answer the KAFSP-Q. Content and face validity was assessed by 6 experts who are knowledgeable in this field and 15 AF patients, respectively. The KAFSP-Q had good CVI and were well understood by AF patients. The KAFSP-Q also had good reliability and stability with Cronbach’s α of .83 and intraclass correlation coefficient values in test-retest for stability of .9. The EFA results indicated that there were 6 factors with factor loadings above .30. The low correlations between subscales ranged between .01 and .48, which indicated that good discriminant and construct validity were achieved. The scale was able to differentiate between patients’ knowledge levels before and after counseling given. Conclusions: The KAFSP-Q is reliable and valid to measure patients’ KAFSP. Further validation studies are recommended to validate the KAFSP-Q in different contexts and in other languages.